2007
DOI: 10.1177/0003319706297647
|View full text |Cite
|
Sign up to set email alerts
|

Local Heparin, Superficial Vein Thrombosis

Abstract: Local, topical effects of heparins on the skin still need deeper investigations. The lack of evidence is mainly due to the lack of large investments in this field. Three main local actions of heparin on the skin can be defined: (1) the anticoagulant action, (2) the microcirculatory-modulatory action determining important control of the microcirculation in case of excessive vasoconstriction or vasodilatation, and (3) the "facilitatory action" on skin permeability, allowing other drugs to diffuse better and fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It may also decrease local thrombogenecity and hence the recurrence, and in addition it may improve the spontaneous lysis of the local thrombosis. It was found that reduction in thrombus size in patients with locally applied heparin occurred 3 times faster than other patients after two weeks.the heparin used in the research was, liposomal spraygel heparin [5]. Another RCT study published showed that the use of Essavin Gel (contains aescin, heparin and essential phospholipids); on a skin with venous hypertensive microangiopathy improves the local microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…It may also decrease local thrombogenecity and hence the recurrence, and in addition it may improve the spontaneous lysis of the local thrombosis. It was found that reduction in thrombus size in patients with locally applied heparin occurred 3 times faster than other patients after two weeks.the heparin used in the research was, liposomal spraygel heparin [5]. Another RCT study published showed that the use of Essavin Gel (contains aescin, heparin and essential phospholipids); on a skin with venous hypertensive microangiopathy improves the local microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…[1–37] Locally acting anticoagulants/antithrombotics have a positive effect on both pain as well as reduction of the size of the thrombus and systemic oral anticoagulation is rarely requested. [79]…”
Section: Discussionmentioning
confidence: 99%
“…[7910] Following this guideline, the authors considered prescribing in this case, both low molecular weight heparin (Enoxaparin 20 mg/day for five days) and topically applied anticoagulants/antithrombotics in the acute phase while complete laboratory and radiological investigations were conducted. These drugs appear effective in terms of reducing local pain, swelling and redness, increasing the patient's mobility, and in preventing local thrombus growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]7] Locally acting anticoagulants/antithrombotics have a positive effect on both pain as well as reduction of the size of the thrombus and systemic oral anticoagulation is rarely requested. [7,9] Nevertheless, the American College of Chest Physicians and several other consensus documents suggest using low molecular weight heparin (LMWH) to prevent thrombosis in subjects at higher risk, mainly in patients with primary superficial thrombosis, which may be associated with other more severe underlying diseases. [7,9,10] Following this guideline, the authors considered prescribing in this case, both low molecular weight heparin (Enoxaparin 20 mg/day for five days) and topically applied anticoagulants/antithrombotics in the acute phase while complete laboratory and radiological investigations were conducted.…”
Section: Discussionmentioning
confidence: 99%